Aggregation-induced phosphorescent emission-active Ir(iii) complexes with a long lifetime for specific mitochondrial imaging and tracking. Issue 7 (22nd January 2020) - Li, Yang; Ma, Bo; Long, Yugui; Song, Ze; Su, Jianyuan; Wang, Yu; Liu, Rui; Song, Guangliang; Zhu, Hongjun
Abstract : Ir(iii ) complexes have been widely used in bio-imaging, photocatalysis and chemical sensing. Five cyclometalated Ir(iii ) complexes (Ir1–Ir5 ) were synthesized and characterized. Abstract : Ir(iii ) complexes have been widely used in bio-imaging, photocatalysis and chemical sensing. Five cyclometalated Ir(iii ) complexes (Ir1–Ir5 ) were synthesized and characterized. Among them, Ir2, Ir3 and Ir4 can exhibit high luminescence efficiency and relatively long phosphorescence lifetimes. Ir2, Ir3 and Ir4 are suitable for imaging and tracking of mitochondria due to their better photostability and luminescence quantum yields compared to commercially available mitochondrial trackers. Ir2, Ir3 and Ir4 displayed significant aggregation-induced emission behaviors from restricted intramolecular motion. Confocal microscopy showed that these complexes accumulate selectively in the mitochondria. Cell cytotoxicity investigations revealed that the Ir(iii ) complexes showed negligible cytotoxicity at the concentrations used. Our study provides insight into the relationship between the structure and the physical properties. These results indicate that these Ir(iii ) complexes are suitable for mitochondrial imaging in living cells.